Analisis Current Ratio, Debt To Equity Ratio, Dan Earning Per Share terhadap Harga Saham: Studi Keuangan pada Sektor Teknologi yang terdaftar di Bursa Efek Indonesia Pada Tahun 2022 - Mita Tri Utami; Jhoansyah, Dicky; Ramdan, Asep Muhamad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The current economic and information technology disruption has a huge impact on many business sectors. This study aims to determine the effect between current ratio, debt to equity ratio, and earning pershare on Stock Price. The methods used in this research are descriptive and associative methods through a quantitative approach. Data analysis using multiple linear analysis with SPSS application. The population in this study were 46 issuers of Technology Sector Companies listed on the Indonesia Stock Exchange in 2022. The sample used in this study amounted to 32 technology sector issuers listed on the Indonesia Stock Exchange in 2022 which were obtained using Purposive sampling technique. The research data used in this study include primary data and secondary data, namely observation, interviews, questionnaires, literature studies, and documentation. The results of this study There is a significant influence of Current Ratio, Debt to Equity Ratio and Earning Pershare on Stock Price.